Dicopper(ii) tetrapyridyl complexes incorporated with ancillary ligands for effective water oxidation. (8th July 2020) - Pi, Wen-Hui; Li, Qi-Jun; Wu, Min; Zhou, Xiao-Lin; Wei, Jia-Ni; Zhu, Xian-Hong; Zhang, Hua-Xin
Abstract : Water oxidation catalysis of dicopper(ii ) tetrapyridyl complexes under alkaline conditions was improved by diamine ligands. Abstract : The water oxidation reaction (WOR) is a bottleneck in water splitting. Though many catalysts have been developed for this reaction, cost-effective, robust and efficient electrocatalysts based on non-precious metals are still highly desired. Herein reported are the synthesis, characterization and electrocatalytic properties of a dicopper(ii ) complex of the tetrapyridyl ligand N, N, N ′, N ′-tetrakis(2-pyridylmethyl)-1, 4-butanediamine (tpbn) and 2, 2′-bipyridine (bpy), [Cu2 (tpbn)(bpy)2 ](ClO4 )4 ·2CH3 COCH3 (1 ). The X-ray single crystallography analysis revealed that the tpbn ligand bridges two copper(ii ) centers located in a square pyramidal environment composed of one bpy ligand as well as two pyridyl and one amino groups of a tpbn. Complex 1 was a molecular electrocatalyst for WOR in 0.1 M NaOAc–NaOH solutions of pH 11.0–14.0. It was demonstrated that the incorporation of the ancillary ligand bpy into the tpbn-bridged dicopper(ii ) complex is crucial for the stabilization of the catalytic system and the enhancement of the activity. This work provided an alternative to achieve robust homogeneous catalytic systems with better performance.